(untitled) (Journal of the College of Basic Education, 2025)
The study involves the preparation of nanocomposites decorated with pharmaceutical compounds and their evaluation for biological effectiveness. These composites primarily utilize materials such as graphene and reduced graphene oxide (RGO). The research highlights the synthesis of these materials, their characterization through various techniques like X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), and Atomic Force Microscopy (AFM), and their application in antibacterial medical masks and bacterial biological activity evaluation. The results show that the nanocomposites have strong antibacterial properties against both gram-positive and gram-negative bacteria. At higher concentrations, they showed higher inhibition rates than regular antibiotics.